Intact Procedural Knowledge in Patients with Alzheimer's Disease: Evidence from Golf Putting. Issue 3 (4th May 2018) - Chauvel, Guillaume; Maquestiaux, François; Gemonet, Elise; Hartley, Alan; Didierjean, André; Masters, Rich; Dieudonné, Bénédicte; Verny, Marc; Bier, Nathalie; Joubert, Sven
ABSTRACT: Can Alzheimer's disease (AD) patients efficiently learn to perform a complex motor skill when relying on procedural knowledge? To address this question, the authors compared the golf-putting performance of AD patients, older adults, and younger adults in 2 different learning situations: one that promotes high error rates (thus increasing the reliance on declarative knowledge) or one that promotes low error rates (thus increasing the reliance on procedural knowledge). Motor performance was poorer overall for AD patients and older adults relative to younger adults in the high-error condition but equivalent between similar groups in the low-error condition. Also, AD patients in the low-error condition had better performance at the final putting distance relative to those in the high-error condition. This performance facilitation for AD patients likely stems from intact procedural knowledge.